Christus Medicus in der frühchristlichen Sarkophagskulptur : ikonographische Studien der Sepulkralkunst des späten vierten Jahrhunderts - Knipp, David. (Vigiliae Christianae, Supplements, 1998)
This study deals with the representation of Christ's Healing Miracles in early Christian sepulchral art from Provence and Northern Italy. It sees the imagery through the contemporary exegetical writings and tries thus to uncover new strata of symbolic significance in early Christian art. The aim of the work is to reveal the complex theological concepts reflected in the relief decoration of a small number of late fourth-century sarcophagi and to cast thus light upon the spiritual climate of the sphere the persons who commissioned them were part of. It also links the narrative structure of representations of medical treatment and miracle scenes in ancient art with the Christian images and establishes new formal and iconographic connexions.